“Jangan Di-Read!”: Indonesian Affixation to English Words on Social Media - Budiarti, Dian; Faris, Ihsan Nur Iman (Universitas Dian Nuswantoro, 2023)
Code mixing has been widely studied, but the study of it focusing on Indonesian affixation to English words is still scant. Therefore, this study aims at investigating the types of affixes, the change in English word classes, and the morphophonemic processes that occurred on social media, specifically on Instagram. Simak method was employed to collect 90 Indonesian affixed-English words from 3 Instagram users’ photo captions as the data. Furthermore, Kridalaksana (2007) and Ramlan’s (2001) theories of affixation were employed to analyze the data. The findings demonstrate that the most frequently used affix is a prefix, with di- recorded as the highest number. As for the lexical function formed after the process of affixation, this study reveals three forms, namely (a) verb-forming, (b) adjectival-forming, and (c) noun-forming with verb-forming is the most frequently used. Finally, in terms of its morphophonemic processes, it is more common that the base form of the English words is maintained rather than considering the phonological rules as regulated in the Indonesian language. These preliminary findings suggest that such affixation does not consider EYD V due to the informal setting the social media mostly constructs.